From Religious Doctrine to Constructive Dialogue: A Phenomenological Analysis of Religious Moderation Practices among NU and Muhammadiyah Students - Partono; Safinatun Naja; Muh Amirudin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to describe the lived experiences of NU and Muhammadiyah students in practicing religious moderation at UIN Sunan Kudus through a phenomenological approach. It reveals how students understand, internalize, and negotiate between their organizational religious doctrines and the demands of constructive dialogue within the dynamics of campus social life. The research employs a qualitative descriptive method, with data collected through in-depth interviews using purposive sampling techniques, participatory observation, and documentation involving students affiliated with NU and Muhammadiyah organizations. The validity of the data was ensured through triangulation of sources, methods, and theories. Data were analyzed through the processes of reduction, presentation, and conclusion drawing. The findings indicate that NU and Muhammadiyah students are able to demonstrate inclusive awareness in interpreting the concept of religious moderation within the dynamic context of pluralistic campus dialogue. The novelty of this study confirms that religious moderation is not only relevant in interreligious settings, but also significantly contributes to strengthening intra-religious moderation to prevent conflict and foster harmonious communities. It further recommends enhancing religious moderation programs through student-based activities.